Research trend on TPACK through bibliometric analysis (2015-2019) - Nadi Suprapto; Sukarmin Sukarmin; Rinie Pratiwi Puspitawati; Erman Erman; Dian Savitri; Chih-Hsiung Ku; Husni Mubarok (International Journal of Evaluation and Research in Education (IJERE), 2021)
This paper aims to analyze the scientific trend of research on Technological Pedagogical Content Knowledge (TPACK) through bibliometric study and explore how the contribution of Indonesian researchers in the Scopus database from 2015 to 2019. The sample was composed of 2075 documents in total. The results revealed that scientific publication on TPACK has been increasing. United States contributed the most documents on TPACK as well as Singapore’s institutions dominated in this area. Meanwhile, Indonesia put its two representative’s institutions: Universitas Sebelas Maret and Universitas Pendidikan Indonesia, among the big ten institutions in the world. All Indonesian documents produced by teacher-producing universities and public universities. United States and Taiwan have also contributed to the most productive authors of TPACK. Then, the visualization of research trend on TPACK resulted in four major clusters: i) TPACK as a system; ii) TPACK in relating to its scale; iii) TPACK in connecting with quantitative parameters; and iv) TPACK under beliefs, intention, and technology acceptance. The research findings could aid related researchers to recognize the trend of TPACK research and recommend directions for further research.